2013
DOI: 10.1007/s10875-012-9859-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Intracellular p47phox and p67phox by Flow Cytometry; Useful Screening Tests for Chronic Granulomatous Disease

Abstract: Chronic granulomatous disease (CGD) is caused by defects of NADPH oxidase.The diagnosis of CGD can be made by analysis of NADPH oxidase activity, however, identification of the CGD subgroups is required before performing mutation analysis. The membrane-bound subunits, gp91phox and p22phox, can be quickly analyzed by flow cytometry, unlike the cytosolic components, p47phox and p67phox. We evaluated the feasibility of flow cytometric detection of p47phox and p67phox with specific monoclonal antibodies in two pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…The role of molecular testing in CGD diagnosis and genetic counseling can be limited with the availability of the needed facilities and expertise in testing laboratories . Identification of CGD subgroups by flow cytometry has been an interest of Wada et al who demonstrated that p47 phox and p67 phox subunits can be analyzed by flow cytometry. These techniques can represent an important secondary screening test for CGD and can be utilized to predict underlying genetic mutations and direct molecular testing.…”
Section: Discussionmentioning
confidence: 99%
“…The role of molecular testing in CGD diagnosis and genetic counseling can be limited with the availability of the needed facilities and expertise in testing laboratories . Identification of CGD subgroups by flow cytometry has been an interest of Wada et al who demonstrated that p47 phox and p67 phox subunits can be analyzed by flow cytometry. These techniques can represent an important secondary screening test for CGD and can be utilized to predict underlying genetic mutations and direct molecular testing.…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic flow cytometric methods to detect phagocyte oxidase subunits have been developed but are not yet generally available. 539 Ultimate confirmation is done by testing for the genetic mutation in the genes that make up the NADPH (reduced form of nicotinamide adenine dinucleotide phosphate) oxidase complex (gp91phox, p22phox, p47phox, p67phox, and p40phox). 540 Summary statement 153.…”
Section: Defects Of the Respiratory Burst Chronic Granulomatous Disementioning
confidence: 99%
“…The detection of LPS‐induced monocyte cell death is useful for rapid diagnosis of CAPS . Intracellular staining is a useful tool for rapid diagnosis of FHL and CGD .…”
Section: Current Treatment Approachesmentioning
confidence: 99%